2013
DOI: 10.4187/respcare.02446
|View full text |Cite
|
Sign up to set email alerts
|

High-Frequency Chest Wall Compression Therapy in Neurologically Impaired Children

Abstract: BACKGROUND: Children with neurological impairment often suffer from insufficient airway secretion clearance, which substantially increases their respiratory morbidity. The goal of the study was to assess the clinical feasibility of high-frequency chest wall compression (HFCWC) therapy in neurologically impaired children with respiratory symptoms. METHODS: This was a single-center, investigator initiated, prospective study. Twenty-two subjects were studied for 12 months before and 12 months after initiation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…22 These techniques effectively clear the central airways of secretions but may be ineffective at mobilizing secretions from more peripheral airways. As a result, various mucus-mobilization techniques like intrapulmonary percussive ventilation [23][24][25] and high-frequency chest-wall compressions (HFCWC) [26][27][28] have been used to enhance the movement of secretions from the peripheral to the more central airways where they can then be coughed out or suctioned. Investigators have also tried altering the properties of mucus to make it easier for the patient to cough secretions out with a variety of inhaled medications, especially when secretion retention leads to lobar atelectasis.…”
Section: Methods To Enhance Airway Clearancementioning
confidence: 99%
See 2 more Smart Citations
“…22 These techniques effectively clear the central airways of secretions but may be ineffective at mobilizing secretions from more peripheral airways. As a result, various mucus-mobilization techniques like intrapulmonary percussive ventilation [23][24][25] and high-frequency chest-wall compressions (HFCWC) [26][27][28] have been used to enhance the movement of secretions from the peripheral to the more central airways where they can then be coughed out or suctioned. Investigators have also tried altering the properties of mucus to make it easier for the patient to cough secretions out with a variety of inhaled medications, especially when secretion retention leads to lobar atelectasis.…”
Section: Methods To Enhance Airway Clearancementioning
confidence: 99%
“…Small studies in children with a variety of neuromuscular or neurological diseases have compared health-care utilization before and after HFCWC use. [26][27][28]79 Seven subjects with quadriplegic cerebral palsy demonstrated a significant reduction in episodes of pneumonia and more effective airway suctioning, defined as suctioning attempts in which sputum was recovered, in the 12 months after use of HFCWC compared with the 12 months before. 28 Furthermore, none of the subjects experienced adverse events resulting from HFCWC use.…”
Section: High-frequency Chest-wall Compressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vibration of the chest wall produces oscillatory airflow, which, in turn, promotes mobilization of secretions from the distal airways toward the mouth. 58 HFCWO decreased the number hospitalizations, physician visits, and antibiotic use in a 1-year study of patients with FD. Regular use of the vest was associated with improved oxygen saturation.…”
Section: Respiratory Treatmentsmentioning
confidence: 96%
“…5 In patient populations in which generating an effective cough is problematic, the role of HFCWC is unclear. Fitzgerald et al 6 hypothesized that adherence to a long-term airway clearance regime including HFCWC in the home improves morbidity due to respiratory infections and reduces the number of hospitalizations for children with neurological impairment who are unable to generate an effective cough. Although the study demonstrated a reduction in the number of hospitalizations after initiation of HFCWC, the outcomes cannot be generalized due to small sample size (N ϭ 7), minimum study power, and lack of randomization.…”
Section: Hfcwcmentioning
confidence: 99%